Drugs in palliative care - Dickman, Andrew (Oxford ; New York : Oxford University Press, 2010)
'While palliative care has adopted a holistic approach to treatment, medication driven symptom management ostensibly forms the critical aspect of care. Pharmacological therapy can be extremely complex because these patients often have co-existing medical conditions in addition to symptoms caused by their terminal disease. The resulting polypharmacy can be daunting for professionals and can negatively impact on effectiveness of care.The practitioner requires a simple, easy to navigate reference source that provides succinct and pertinent drug information. This detailed yet concise handbook will appeal to a variety of healthcare professionals involved in the provision of palliative care and medicines information. It begins with an overview of pharmacology and prescribing advice then contains over 100 entries of palliative care drugs, in an easy to use A-Z format'--Provided by publisher
Clinical pharmacology overview --Prescribing guidance - Drug monographs A-Z
Keywords: Pain -- drug therapy -- handbooks; Analgesics -- therapeutic use -- Handbooks; Palliative Care -- methods -- Handbooks